Education on Supplementary Feeding and Types of Local Food for Pregnant Women with Chronic Energy Deficiency in the Work Area of Paccerakankang Health Center Makassar City - Henny Henny; Hasmah Hasmah; Musfirah Musfirah (Journal of Global Nutrition, 2022)
Pregnant women are a group that is vulnerable to health problems including Chronic Energy Deficiency (CED). Knowledge of pregnant women about the provision of supplementary food and types of local food is very important for pregnant women to know so that their nutritional intake is adequate. This study aims to determine the education of supplementary feeding and local food sources for pregnant women with chronic energy deficiency in the working area of ​​the Paccerakg Health Center Makassar City. This research is a descriptive research with group extension method. Data collection begins in June-July 2021. The sample in this study uses a total sampling of 31 respondents. The results of this study indicate that from the group of respondents with knowledge of CED after the pre-test, there are 22.6% and after the post-test there are 90.3% with good knowledge. The group of respondents with knowledge of supplementary feeding, after the pre-test there were 64.5% and after the post-test there were 90.3% with good knowledge. The group of respondents with knowledge of local food types after the pre-test was 19.4% and after the post-test there were 90.3% with good knowledge. After education about CED, supplementary feeding and types of local food for pregnant women, there was an increase in knowledge.